2018
DOI: 10.1016/j.toxrep.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Acetonic extract of Vernonia amygdalina (Del.) attenuates Cd-induced liver injury: Potential application in adjuvant heavy metal therapy

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 53 publications
3
28
0
Order By: Relevance
“…Histological examinations of the liver of the rats in the control group revealed evidence of apparently normal liver histoarchitecture characterized by normal parenchymal structure, intact lamellar pattern of the hepatocytes and Kupffer cells, and normal sinusoidal architecture, and no significant lesions were observed, similar to a work by Imafidon et al [13]. Likewise, the kidney of the control group showed normal renal histoarchitecture characterized by normal glomerulus structure, capsular space, normal macula densa, and normal tubular architecture.…”
Section: Discussionsupporting
confidence: 84%
“…Histological examinations of the liver of the rats in the control group revealed evidence of apparently normal liver histoarchitecture characterized by normal parenchymal structure, intact lamellar pattern of the hepatocytes and Kupffer cells, and normal sinusoidal architecture, and no significant lesions were observed, similar to a work by Imafidon et al [13]. Likewise, the kidney of the control group showed normal renal histoarchitecture characterized by normal glomerulus structure, capsular space, normal macula densa, and normal tubular architecture.…”
Section: Discussionsupporting
confidence: 84%
“…These enzymes are located in the liver cells and released into the plasma in response to the liver cell injury or damage. ( Imafidon et al., 2018 , Ozer et al., 2008 ). In the present study, after the Cd administration, the activity of GOT was significantly elevated in the 15.56-, 30.55-, and 60.67-mg Cd/kg groups.…”
Section: Discussionmentioning
confidence: 99%
“…It could also be a mixture of some of these effects since the products have been stated to comprise three to five different herbal plants with different pharmacological properties. The argument for a possible liver protective effect by HPC is partly supported by previous studies which found one of the active ingredient of HPC 'Phyllanthus fraternus' to possess antihepatotoxic activity [32,33], justifying its used in traditional medicine for the treatment of jaundice. This assertion on HPC also correlates well with a clinical trial of the same product which was published at the time this current study was ongoing [34].…”
Section: Discussionmentioning
confidence: 94%